Does Cesarean Section Increase the Risk of Postpartum Depression? A Systematic Literature Review - Alrika Febi Yuarsyah; Budi Utomo; Izzati Dwi (Journal of Midwifery, 2021)
Background: Postpartum depression (PPD) is a psychological disorder experienced by mothers at 4 weeks to 6 months postpartum. One of the risk factors for postpartum depression is the type of delivery. The mode of delivery in its effect on postpartum depression has been studied extensively with conflicting results whether vaginal delivery or cesarean section (CS) that can affect postpartum depression (Rauh et al., 2012). Methods: This is a systematic literature review with a research question using PICO standard namely "What is the correlation between mode of delivery and postpartum depression?". 325 literature were obtained from five different databases. The screening was carried out according to PRISMA flowchart and bringing in a total of 21 literature to be reviewed. Results: Most of the literature reported that mothers with CS have higher EPDS scores than mothers with vaginal delivery. One literature stated that mothers with CS were more protected and less prone to PPD, and other studies stated that the method of delivery was not associated with PPD. Conclusion: Delivery mode is associated with postpartum depression in most studies. Mothers with CS are more at risk of exposure to PPD than mothers with vaginal delivery